Modelling public transport mode choice for low-income residential suburbs in Harare, Zimbabwe - Mapfurira, Masimba Tutsirai (Department of Civil Engineering, 2023)
Modern-day life in developing urban cities is structured around the need to access goods and services outside the vicinity of residential areas, and transportation facilitates access to such services. Like many other African cities, most of the residents in Harare sorely rely on public transport, and while the government of Zimbabwe acknowledges the need for efficient public transportation systems in the country's urban environments, insufficient commitment and political will have been directed towards developing strategic plans with clear and well-defined objectives. The development of public transport plans and policies requires a good understanding of the passengers' service quality needs and willingness to pay for service quality improvements. In this study, we use stated choice preference data collected from five high-density suburbs in Harare (n = 361) to investigate the influence of service quality indicators to travel mode choice decisions. Multinomial, mixed, and latent class logit models are developed under the random utility maximisation framework and compared to identify the best model. The model is used to evaluate the willingness to pay indicators for public transport service improvements and outline the contributions of the findings to possible policy directives. The results suggest that latent class models better explain observed choices than mixed and multinomial logit counterparts. With regards to public transport mode choice behaviour, the study classifies the population into two distinct groups on the basis of gender, income, employment status, and location. The willingness to pay indicators shows a substantial difference in the value of all the public transport attributes between the groups, except for waiting time. The willingness to pay for improvements in waiting time, which relates to service frequency, is standard at Z$65 per hour. Noteworthy is the classification of the suburbs between the groups; the posterior analysis indicates that Chitungwiza residents have the highest willingness to pay and Budiriro, the least. This research is of value to ZUPCO and other potential private players in identifying service quality deficiencies and understanding the requirements of public transport service provision at the suburban level. The strong inertia towards kombis emphasises the general dissatisfaction with ZUPCO service quality levels while providing insights into lagging areas that future policy deliberations could address. The research presents a potential performance framework to the Harare city council against which the public transport service provision can be assessed. Most importantly, the findings might be useful in further understanding the public transport landscape in other cities in Zimbabwe, similar to the high-density suburbs used as study areas in this research.